2008
DOI: 10.1001/archneurol.2007.56
|View full text |Cite
|
Sign up to set email alerts
|

Protein Misfolding and Neurodegeneration

Abstract: key molecular pathway implicated in diverse neurodegenerative diseases is the misfolding, aggregation, and accumulation of proteins in the brain. Compelling evidence strongly supports the hypothesis that accumulation of misfolded proteins leads to synaptic dysfunction, neuronal apoptosis, brain damage, and disease. However, the mechanism by which protein misfolding and aggregation trigger neurodegeneration and the identity of the neurotoxic structure is still unclear. The aim of this article is to review the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
207
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(211 citation statements)
references
References 64 publications
(106 reference statements)
1
207
1
2
Order By: Relevance
“…7C, F). The presence of polyubiquitinated aggregates is an hallmark of neurodegenerative diseases [37,38] including Alzheimer's Disease, Parkinson's Disease and Amyotrophic Lateral Sclerosis (ALS). Thus we have investigated Epoxomicin's effects on an in vitro model of ALS.…”
Section: β-Estradiol and Epoxomicin Impact On Primary Spinal Cord Culmentioning
confidence: 99%
“…7C, F). The presence of polyubiquitinated aggregates is an hallmark of neurodegenerative diseases [37,38] including Alzheimer's Disease, Parkinson's Disease and Amyotrophic Lateral Sclerosis (ALS). Thus we have investigated Epoxomicin's effects on an in vitro model of ALS.…”
Section: β-Estradiol and Epoxomicin Impact On Primary Spinal Cord Culmentioning
confidence: 99%
“…Although accounting for only a small percentage of all ALS cases, SOD1 mutations represent one of the main known causes of the disease. The similar symptoms and pathology of familial and sporadic ALS suggest common disease mechanisms and the potential for related therapeutic strategies (1)(2)(3). The mechanisms by which mutant SOD1 causes ALS are not known; however, extensive evidence supports a toxic gain of function due to increased aggregation of mutant protein.…”
mentioning
confidence: 99%
“…The mechanisms by which mutant SOD1 causes ALS are not known; however, extensive evidence supports a toxic gain of function due to increased aggregation of mutant protein. Misfolding and aggregation of diverse proteins are observed in numerous diseases, including other neurodegenerative diseases such as Alzheimer's, Huntington, and prion diseases (1,2). Amyloid is a type of aggregate structure formed by many disease-associated proteins, and perhaps by all proteins, often under destabilizing conditions (4).…”
mentioning
confidence: 99%
“…Many neurodegenerative diseases involve accumulation of intracellular aggregates of misfolded protein, implying that defects in protein processing may be linked to their development and pathogenesis (1,2). Molecular genetic studies have identified a number of intracellular proteins involved in these processes, and these may ultimately prove useful as targets for therapeutic drug development (3).…”
mentioning
confidence: 99%